MANAGEMENT OF DIGITAL ART STARTUPS IN THE AI ERA - Pandey, Sonia; Nair, Prabha Shreeraj; Gupta, Anchal; wadhwa, Charu; Kalra, Hitesh; Gupta, Ravina; Khemnar, Vijaya Ravsaheb (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The recent aggressive adoption of the creative economy by Artificial Intelligence (AI) has transformed how digital art startups are run, funded, and even their morals. The article provides a detailed pattern of how AI-driven creative businesses should be governed and concentrates on the interplay of the technological factor, creativity as an art, and responsible management. The study by conceptualizing, empirically investigating and case based evidence identifies strategic aspects that involve AI augmented creativity, hybrid leadership, data-driven infrastructure, and sustainable financial modelling as the key elements to establish competitiveness in digital art industry. These findings show that the startups that apply the human-AI cooperation are more scalable, effective in the dimension of innovation and attract the audience in comparison with the traditional ones. However, these benefits have been pegged on the availability of strong governance structures to address algorithmic bias, intellectual property and cultural sensitivities. The article proposes a single management framework, which would align the creative procedure to the anticipatory analytics, blockchain openness, and moral AI management. That combination of theoretical and empirical knowledge enables the research to contribute to the existing discourse of the sphere of digital entrepreneurship and to suggest the practical opportunities of how the innovative businesses may evolve in the AI age in a responsible manner.